2004
DOI: 10.1017/s1537592704040241
|View full text |Cite
|
Sign up to set email alerts
|

Is Gender like Ethnicity? The Political Representation of Identity Groups

Abstract: Some 50 countries officially allocate access to political power by gender, ethnicity, or both. Yet in the world's electoral democracies, the policies used for women differ systematically from those used for ethnic groups. The former receive candidate quotas in parties; the latter, reserved seats in legislatures. Why? My explanation focuses on the varying ways that gender and ethnic identities intersect with partisan cleavages and on the distinct "work" performed by the different remedies for underrepresentatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
159
0
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 240 publications
(171 citation statements)
references
References 36 publications
0
159
0
6
Order By: Relevance
“…Although normative theorists often compare arguments for the representation of different groups (e.g., Kymlicka [1995]; Mansbridge [1999], Young [2000]), there have been relatively few systematic empirical comparisons of how quotas are designed for women and minority groups (but see Htun [2004]; Krook & O'Brien [2010]). …”
Section: Groups and Representation: Problems And Solutionsmentioning
confidence: 99%
See 3 more Smart Citations
“…Although normative theorists often compare arguments for the representation of different groups (e.g., Kymlicka [1995]; Mansbridge [1999], Young [2000]), there have been relatively few systematic empirical comparisons of how quotas are designed for women and minority groups (but see Htun [2004]; Krook & O'Brien [2010]). …”
Section: Groups and Representation: Problems And Solutionsmentioning
confidence: 99%
“…Analyzing electoral democracies, she points out that different types of quotas are adopted for women versus minority groups (Htun 2004). …”
Section: Groups and Representation: Problems And Solutionsmentioning
confidence: 99%
See 2 more Smart Citations
“…As Mügge and Erzeel (forthcoming) observe, an intersectional framework allows us to understand the power dynamics underpinning the various mechanisms at work in the political recruitment process; moreover, it can help reveal identities that are particularly advantaged or disadvantaged by formal and informal representational norms and values. To date, gender and race has been the principle intersection that has been studied; in particular the underrepresentation of women of colour (Htun, 2004;Hughes, 2011;Minta, 2012;Strolovitch, 2006;Reingold and Smith, 2012). Studies in the US have suggested that women of colour have more electoral ambition than white women (Moore, 2005) with women of colour making the majority of electoral gains made by women in recent years (Hardy-Fanta et al, 2006).…”
mentioning
confidence: 99%